Mother, Memory, Monotony - Osborn, Joshua (My University, 2017)
Joshua Caleb Osborn is a second year Master’s student in Creative Writing and Poetics at the University of Washington Bothell. His work hybridizes genre through sound and affect, attempting to produce a more poetic prose, or more prosaic poetry, particularly in performative and vocal environments. His thesis continuously wanders around a central premise: the immanence of his mother’s death. Caught between reality, dream, and memory the speaker seeks to preserve or repossess the identity of a mother who is no longer capable of preserving or possessing her own. The speaker’s relentless attempts to locate or define her fall desperately short, and it’s those very failures that inhabit the page as a consequence. His writing process is self-described as ‘apocalyptic’ in the Greek sense of the word, literally meaning ‘an uncovering,’ or revelation of knowledge. “Revelation is gradual and unending: it calls attention to the processes by which the truth it speaks of is revealed.” He’s interested in the capacities of language as a truth-bearing faculty, in the powers of belief and reason, and the frictions that warp secular and religious institutions. How is it—there are so many ways of telling the truth?
Thesis (Master's)--University of Washington, 2017-06
Keywords: Creative Writing; English; Fiction; Memory; Mother; Creative writing; Pedagogy; English